All About Extra Ocular Muscles: Easy to Understand - Chowdhury, Pertha Haradhan; Shah, Brinda Haren; Tiwari, Nripesh (International Journal For Research In Health Sciences And Nursing, 2020)
This paper describes about Anatomy and Physiology of Extra Ocular Muscles.